Pharmaceuticals companies’ promotional brochures: do they display reliable and useful medications’ information? - Idris, Kamal Addin Mohammad Ahmad; Yousif, Mirghani Abdulrahman; Mustafa (late), Asim Faroug (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The main objective of this study which was the first of its kind in Sudan was the evaluation of the medication informational contents (section headings) of pharmaceutical companies’ promotional brochures, their possible benefits, reliability and usefulness in the proper and rational use of drugs. Methods: Three hundred and fifty-one (n=351) brochures were collected from randomly selected doctors’ clinics in Khartoum, Sudan. Ninety-two of those brochures were excluded for being either duplicates, reminder brochures, promoting medical devices or cosmetics. The remaining (259), were then screened to match their macro-informational contents (section headings) against same advised in world health organization ethical criteria for medicinal drug promotion. Results: Almost all the screened brochures displayed unbalanced and poorly evidence supported (48.2%) medication information messages, which minimized the risks of the promoted drugs (45.4%), while displaying section headings encouraging more use of the promoted products, in higher frequencies (93.66%).There was significant difference between the frequencies of display of medication information section headings of eight out of nine tested section headings, of a multinational and branded generic brochures (p. value ranged between 0.01 and 0.000). Conclusions: Screened brochures were found to display poorly reliable and unbalanced medication information. Healthcare providers shall, accordingly, seek independent medication information sources, and not solely depend on commercial sources of medication information. Official regulators shall strictly define and mandate medication information contents in printed pharmaceutical promotional materials. Healthcare providers should, also, master the skills of appraising such promotional printed materials if rational medication use is to be achieved.